THE USE OF DEIXIS PERSONA OF SINGULAR SECOND PRONOUNS IN SIDOARJO FROM THE PERSPECTIVE OF SOCIOLINGUISTICS'S DIMENSIONS - Istianatul Hikmah (University of Kuningan, 2017)
The study analyzes the use of deixis persona of singular second pronouns in daily conversation in Sidoarjo. This study applied a qualitative descriptive method. The theory of sociolinguistics's dimension proposed by Holems (1997) and deixis persona by Yule (2006) are used in this study. As results, the study concludes two things; (1) there are six deixis persona of singular second pronouns that are usually used in Sidoarjo society in their daily conversation, those are panjenengan, njenengan, sampeyan, peyan, awak mu, and koen; then there are three deixis persona of singular second pronouns that are seldom used by Sidoarjos society, those are peno, ente, and koe; and (2) there are three sociolinguistics's dimensions which influence the use of deixis persona of singular second pronouns namely solidarity, power, and situation.Keywords: deixis persona, singular second pronouns, sociolinguistics's dimensions, Sidoarjo society